Hung Nguyen on food safety - Hung Nguyen-Viet (International Food Policy Research Institute, 2014)
Hung Nguyen, Hanoi School of Public Health, at the side event, "Food Safety: Options for Addressing a Growing Crisis." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info